2016
DOI: 10.3109/15412555.2015.1101435
|View full text |Cite
|
Sign up to set email alerts
|

Early COPD Exacerbation Treatment with Combination of ICS and LABA for Patients Presenting with Mild-to-Moderate Worsening of Dyspnea

Abstract: This is a proof of concept study that aims to establish feasibility and safety of a new strategy that includes an action plan for early treatment of acute exacerbations of COPD (AECOPD) with doubling dose of a combination of a long-acting beta2 agonist and an inhaled corticosteroid, and to explore its potential for avoiding the requirement of prednisone and its safety. Thirty-seven COPD outpatients with previous exacerbations were enrolled and followed-up for 12 months. The written action plan included a stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…This might open up the possibility of using long-acting β 2 agonists (LABA) for the treatment of AECOPD [ 43 ]. A proof of concept [ 44 ] performed in AECOPD patients having a mild-to-moderate worsening of dyspnea demonstrated that an early treatment with doubling dose of a combination of a LABA (Salmeterol) plus an inhaled corticosteroid (ICS, Fluticasone Propionate) for 10 days has a potential effect avoiding the requirement of prednisone within 30 days of the onset. In a single-center, open-label, randomized, crossover, and single-blind trial on 12 hospitalized AECOPD patients, a recent study exploring the acute effect of indacaterol found a significant mean increase in FEV 1 and forced vital capacity (FVC), with the highest increase at the dose of 300 mg; however, transient episodes of oxygen desaturation were observed in some patients with relatively well-preserved PaO 2 (− 5.9 mmHg [95% CI -1.4 to − 10.4] and − 6.2 mmHg [95% CI -2.7 to − 9.8] in the mean peak in PaO 2 over 6 h in the group treated with indacaterol 150 mg and indacaterol 300 mg, respectively) [ 45 ].…”
Section: Bronchodilatorsmentioning
confidence: 99%
“…This might open up the possibility of using long-acting β 2 agonists (LABA) for the treatment of AECOPD [ 43 ]. A proof of concept [ 44 ] performed in AECOPD patients having a mild-to-moderate worsening of dyspnea demonstrated that an early treatment with doubling dose of a combination of a LABA (Salmeterol) plus an inhaled corticosteroid (ICS, Fluticasone Propionate) for 10 days has a potential effect avoiding the requirement of prednisone within 30 days of the onset. In a single-center, open-label, randomized, crossover, and single-blind trial on 12 hospitalized AECOPD patients, a recent study exploring the acute effect of indacaterol found a significant mean increase in FEV 1 and forced vital capacity (FVC), with the highest increase at the dose of 300 mg; however, transient episodes of oxygen desaturation were observed in some patients with relatively well-preserved PaO 2 (− 5.9 mmHg [95% CI -1.4 to − 10.4] and − 6.2 mmHg [95% CI -2.7 to − 9.8] in the mean peak in PaO 2 over 6 h in the group treated with indacaterol 150 mg and indacaterol 300 mg, respectively) [ 45 ].…”
Section: Bronchodilatorsmentioning
confidence: 99%
“…To overcome the limitation of the short half-life of b 2 -agonists, use of long-acting b 2 -agonists (LABAs) has been recommended (75). A proof-of-concept study showed that doubling the dose of LABA + inhaled corticosteroids (ICS; salmeterol and fluticasone propionate) for 10 days during the early treatment of AECOPD could reduce the use of prednisone within 30 days of onset in over 75% of patients, thereby decreasing the systemic adverse effect of steroids (76). In a nonblinded, randomized, controlled pilot trial involving 29 patients with AECOPD in the ED, administration of LABA (indacaterol 300 mg once daily) improved lung function compared with traditional therapy without cardiovascular side effects (77).…”
Section: Treatment Of Aecopdmentioning
confidence: 99%
“…Given the complicated onset mechanisms of AECOPD, single-drug therapies in the past have often failed to achieve marked effects when recovering patients' PF indices, whereas some drug combinations used together achieve synergistic effectiveness for enhanced efficacy, PF, and ventilatory capacity (VC) (Bourbeau et al 2016;Kaufman 2017;Rajala et al 2017). Therefore, in order to provide more strategies for treating AECOPD patients, this study compared the clinical efficacies of combination therapy with albuterol and tiotropium bromide with routine treatment by observing and comparing PF changes.…”
Section: Introductionmentioning
confidence: 99%